Achieving Aircraft Pitch Control Through Artificial Intelligence - Ahseen Nasir Aldeeb; Alla Hasan Abdullah (African Journal of Advanced Pure and Applied Sciences, 2024)
One of the biggest challenges in the aircraft field is the pitch control. enhancing the safety of the flight is an important factor. today many aircraft control systems employing classical controllers such as PID controllers that will enhance the system characteristics performance. in the past, the PID was tuned with classical methods such as trial and error and Zeigler Nichols. artificial intelligence now used optimization techniques to representing the possible solutions for a problem. using artificial intelligence for tuning the PID parameters will enhance the system’s stability. The genetic algorithm optimization technique is used for tuning the PID parameters. The result will be compared with trial and error and Zeigler Nichols tunning methods. The results show that artificial intelligence enhanced the performance and stability of the system better than the other tunning methods.